(untitled) (Bangladesh Journal of Medical Education, 2023)
Background: Medical education exposes students to authentic learning situations and need epistemological access to tacit knowledge, skills and practice in order to interpret patient problems. Adopting a new teaching-learning approach is daunting task. Blended learning offers opportunities for the complexity of learning by integrating face-to-face and online interaction. However, this growing demand for blended learning possesses problems and challenges that are noteworthy to investigate, specifically in medical education. Method: This descriptive type of cross-sectional study was conducted to reflect different lenses of experiences by the medical teachers on views of blended leaning in undergraduate medical education in Bangladesh. Data collected from eight medical colleges of Bangladesh. Convenient sampling technique adopted for selection of medical college and the respondents were selected from the medical college purposively. Self-administered semi-structured questionnaire was administered to collect data from 70 medical teachers to gain more details insight related with this research issue. Results: This study revealed out that most teachers owned digital equipments, from smartphones (100%) to laptops (91.4% of teachers), had optimum knowledge and skill in ICT (88.6% of teachers), were using social networking (91.4% of teachers). All (100%) respondents stated that they did not have established e-library facilities and no established Information Technology (IT) laboratory facilities as opined by 43% of teachers in their medical colleges. The data analysis ascertained that the teachers were in affirmative consensus on the components of teaching learning process. By mean scores of 5-point likret scale, satisfying prominent components were listed as organizing teaching process by the teachers (4.3 for teachers) and well design curriculum (4.3 for teachers). In this study, maximum 55.1% of teachers respondents preferred 20-40% of overall online class. Conclusion: The study recommended that a proper framework that integrate policies, curriculum contents alone with technological and electronic innovation matching with blended learning format to stimulate teaching and learning process in the path for successful introduction of blended learning in undergraduate medical education in Bangladesh. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 23-32